Immediate Implant Placement in Anterior Maxilla - Gurung, John; Dhami, Bhageshwar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
This case report describes extraction of a fractured right maxillary lateral incisor tooth which was previously treated endodontically, followed by immediate placement of a dental implant in the prepared socket and temporisation by a removable partial denture. The tooth was extracted with minimal hard and soft tissue trauma. The socket was prepared to the required depth and implant was inserted. An impression was made after four months, and a definitive restoration was placed. The atraumatic operating technique and the immediate insertion of the implant resulted in the preservation of the hard and soft tissues at the extraction site. The patient exhibited no clinical or radiologic complications after loading.